2012
DOI: 10.1175/jtech-d-11-00174.1
|View full text |Cite
|
Sign up to set email alerts
|

Far-Field Power of Lightning Strokes as Measured by the World Wide Lightning Location Network

Abstract: The World Wide Lightning Location Network (WWLLN) is a long-range network capable of locating lightning strokes in space and time. While able to locate lightning to within a few kilometers and tens of microseconds, the network currently does not measure any characteristics of the strokes themselves. The capabilities of the network are expanded to allow for measurements of the far-field power from the root-mean-square electric field of the detected strokes in the 6–18-kHz band. This is accomplished by calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(170 citation statements)
references
References 15 publications
9
159
0
2
Order By: Relevance
“…The analysis reveals that the change in the exponential dependence is connected with the transition from the amplitudes of negative discharges to those of positive discharges, which are known to have higher values of currents running in the lightning channel. The data of the WWLLN network, obtained by the method of Hutchins et al (2012), are used to estimate the signal amplitudes in thunderstorm centers. Thus, in search of the EQ effects and their precursors in the amplitude variations of atmospherics, it was necessary to choose the signals with an amplitude lower than the transition area, but close to it.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis reveals that the change in the exponential dependence is connected with the transition from the amplitudes of negative discharges to those of positive discharges, which are known to have higher values of currents running in the lightning channel. The data of the WWLLN network, obtained by the method of Hutchins et al (2012), are used to estimate the signal amplitudes in thunderstorm centers. Thus, in search of the EQ effects and their precursors in the amplitude variations of atmospherics, it was necessary to choose the signals with an amplitude lower than the transition area, but close to it.…”
Section: Discussionmentioning
confidence: 99%
“…The WWLLN measures the time of group arrival of a sferic relative to GPS time and triangulates a source location using a network of over 50 sensors (Dowden et al, 2002). Hutchins et al (2012) reported WWLLN timing errors to be within 10 microseconds and location accuracies in the order of the wavelength of the radiation (10-15 km). Abarca et al (2010) reported WWLLN detection efficiencies of 30 to 50% for cloud-to-ground strokes (CG) and intra-cloud strokes (IC) above 40 kA, and 10 to 15% for all global CG strokes.…”
Section: Lightning Location Networkmentioning
confidence: 99%
“…Abarca et al (2010) reported WWLLN detection efficiencies of 30 to 50% for cloud-to-ground strokes (CG) and intra-cloud strokes (IC) above 40 kA, and 10 to 15% for all global CG strokes. The WWLLN also provide lightning stroke power estimates integrated over a 1 ms waveform (Hutchins et al, 2012).…”
Section: Lightning Location Networkmentioning
confidence: 99%
“…The sferic attenuation along the path was calculated based on the ionospheric model with regard to the influence of its diurnal variation. In comparison with ground-based lightning data detected by IMPACT-ESP2 sensors over New Zealand, the coefficient of determination (R 2 ) for the estimated peak currents between the two sensors was 0.92 (Hutchins et al 2012a).…”
Section: Datamentioning
confidence: 99%